Skulpturen in der Wandelhalle. (Köln : Forum für Kunst "Die Wandelhalle", 1984)
Marohn, Karl Heinz ; Bell, Victoria ; Sturm, Udo ; Breloh, Heinz ; Pick, Peter ; Schmitt, Klaus ; Bachmayer, Hans Matthäus ; Dupuis, Mary Noële ; Bonvie, Peter
Skulpturen in der Wandelhalle, Forum für Kunst "Die Wandelhalle", Köln, 21. September - 20. Dezember 1984
boek